2012
DOI: 10.1097/qad.0b013e32834fa13d
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal contraception and the risk of HIV acquisition among women in South Africa

Abstract: In this study conducted among South African women, hormonal contraception did not significantly increase the risk of HIV acquisition. However, the effect estimate does not rule out a moderate increase in HIV risk associated with DMPA use found in some other recent studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
75
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 17 publications
6
75
1
1
Order By: Relevance
“…Some recent publications suggest that DMPA use is associated with a significantly higher risk of acquiring HIV (2)(3)(4), although other studies did not find this association (5,6). Use of DMPA has previously also been linked to increased risk of acquisition of other sexually transmitted diseases, such as Trichomonas vaginalis, Neisseria gonorrhoeae, and Chlamydia trachomatis (7).…”
mentioning
confidence: 87%
“…Some recent publications suggest that DMPA use is associated with a significantly higher risk of acquiring HIV (2)(3)(4), although other studies did not find this association (5,6). Use of DMPA has previously also been linked to increased risk of acquisition of other sexually transmitted diseases, such as Trichomonas vaginalis, Neisseria gonorrhoeae, and Chlamydia trachomatis (7).…”
mentioning
confidence: 87%
“…Resultados El riesgo de seroconversión del VIH-1 fue superior en las mujeres que declararon utilizar anticonceptivos hormonales en el momento de la inscripción en el ensayo (índice de riesgos ajustado: 1,24; IC del 95%: 0,97-1,58) que en las mujeres que declararon utilizar otros tipos de anticonceptivos. Entre la población, el uso de anticonceptivos hormonales (píldoras o inyectables) en el punto de partida y durante el seguimiento del estudio representó aproximadamente el 20% (IC del 95%: [16][17][18][19][20][21][22] de las seroconversiones del VIH-1. No obstante, el riesgo parcial atribuible a la población indicó un impacto relativo del 12% (IC del 95%: 9.0-15.7).…”
Section: Introductionunclassified
“…19 Morrison et al combined the multisite data from the Carraguard® trial, including the Durban site data, and showed a moderately increased risk of HIV-1 seroconversion with the use of the injectable progestin depo-medroxyprogesterone acetate, but no effect with other types of hormonal contraceptives. 20 Based on available data, in 2012 the World Health Organization released a technical statement clarifying that the data on hormonal contraceptives was inconclusive and that women should continue to use hormonal contraceptives to prevent unwanted pregnancy. Nonetheless, it advised women using progesterone-only contraception to use condoms and other methods for preventing HIV-1 infection.…”
mentioning
confidence: 99%
“…In a systematic review [67], four of nine studies considered informative but with important limitations reported a 1.5 to 2.2 times increased risk of HIV acquisition in women using injectable contraception(DMPA) [3,28,56,87]. The remaining five studies of injectable contraception in the review [39,57,62,71] reported no statistically significant association with risk of HIV acquisition. In the same review [67], only one study reported increased risk of acquisition resulting from the use of oral contraceptive pills (OCPs).…”
Section: Introductionmentioning
confidence: 99%